Freudian Analysis of Freedom: Comparing 'Aku Perempuan' by Indah Pratama and 'The Sky is the Limit' by Rohini Vij - Tamtama, Rafael Aglis Ariya; Odelia, Risca Jovita; Bunadi, Stefanie Keren; Sriastuti, Anna (Universitas Negeri Semarang, 2024)
This comparative research analyzes the freedom of the main characters in two short stories